STUDY ON SOFTENING AND DROPPING PROPERTIES OF METALIZED BURDEN INSIDE BLAST FURNACE - Bi-yang Tuo; Sheng-li Wu; Li-hua Zhang; Jian-long Wu; Ying Sun (Tecnologia em Metalurgia, Materiais e Mineração, 2014)
The inferences of burden metallization rate on softening-melting dropping properties were investigated through softening-melting dropping test of three kinds of metalized burden pressure drop. The results indicated that the softeningmelting temperature interval of pre-reduction mixed burden is bigger than primeval mixed burden, the melting interval narrow with the rise of metallization rate of ferric burden as well as dropping temperature interval. The average pressure drop, maximum pressure drop and softening-melting dropping properties eigenvalue decrease with the rise of metallization rate of ferric burden. Besides, the dropping temperature of burden reduces with the rise of carbon content of molten iron. The combination high metalized burden and higher carbon content of molten iron is benefit to decreasing thickness of cohesive zone and improve permeability of cohesive zone.